Educational impact of a novel cleft palate surgical simulator: Improvement in surgical trainees' knowledge and confidence. Issue 10 (October 2022) - Nicholas, Rebecca; Heinze, Zavira; Papavasiliou, Theodora; Fiadeiro, Rute; Atherton, Duncan; Timoney, Norma; Echlin, Kezia
Summary: Background: Trainees' experience in cleft surgery is limited due to the high-risk nature of the surgery and centralization of cleft care. Simulation training allows trainees to learn complex surgical tasks whilst ensuring patient safety. Existing cleft surgical simulators are over-simplified or prohibitively expensive. In this article, we show the development and application of a high-fidelity yet cost-effective simulator for cleft palate repair. Methods: Skeletal elements were obtained through high-resolution scanning of a pathologic specimen, 3-dimensional printed, and then molded in plastic. Soft tissue components were formed through molding layers of silicone. The simulator was tested by 26 United Kingdom (UK) specialty trainees who performed a vomerine mucosal flap and intra-velar veloplasty in a 1-hour workshop. Pre- and post-simulation questionnaires assessing cleft knowledge and surgical confidence were compared for statistical significance. Results: The simulator had high acceptability: 23/26 participants confirmed that the simulation training was a valuable learning experience. Baseline experience of cleft palate surgery was low: 24 participants had never performed any part of the procedure before. Following the workshop, mean knowledge score increased by 38%, and confidence by 53%. The paired T-test demonstrated that observed improvements in both knowledge and confidence were statistically significant (p<0.001). Conclusions: Simulation training is increasingly recognized as a crucial component of improving patient safety. Our new cost-effective cleft palate simulator has high acceptability and is a powerful educational tool that is effective in improving cleft palate surgical knowledge and confidence across all grades of surgical trainees.